Detection and quantification of tick-transmitted pathogens from the selected localities of the Czech Republic - Šmejkalová, Zuzana (Jihočeská univerzita, 2015)
Prevalence of tick-borne pathogens (Borrelia and Babesia) in Ixodes ricinus ticks was determined in three localities of the Czech Republic. The pathogens were further classified into genospecies. Quantities of Borrelia spirochetes in nymphs was determined and subsequently compared with results of Borrelia quantification performed on nymphs artificially infected in the laboratory Borrelia transmission model.
Detection and quantification of tick-transmitted pathogens from the selected localities of the Czech Republic
Keywords: tick; Ixodes ricinus; Borrelia; Babesia; tick; Ixodes ricinus; Borrelia; Babesia